2012
DOI: 10.1073/pnas.1200330109
|View full text |Cite
|
Sign up to set email alerts
|

Identification of olivetolic acid cyclase from Cannabis sativa reveals a unique catalytic route to plant polyketides

Abstract: Δ 9 -Tetrahydrocannabinol (THC) and other cannabinoids are responsible for the psychoactive and medicinal properties of Cannabis sativa L. (marijuana). The first intermediate in the cannabinoid biosynthetic pathway is proposed to be olivetolic acid (OA), an alkylresorcinolic acid that forms the polyketide nucleus of the cannabinoids. OA has been postulated to be synthesized by a type III polyketide synthase (PKS) enzyme, but so far type III PKSs from cannabis have been shown to produce catalytic byproducts ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
236
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(255 citation statements)
references
References 41 publications
2
236
1
5
Order By: Relevance
“…Recently, Page's research group discovered an enzyme (olivetolic acid cyclase, OAC), which is inactive itself, but works with TKS to produce olivetolic acid. Interestingly, these two proteins did not physically interact each other to form a protein complex, as was initially hypothesized (Gagne et al 2012). Hop (Humulus lupulus L.), which also belongs to the Cannabaceae family, is an essential component, along with barley and yeast, for the beer brewing industry.…”
Section: Phenylpropanoids and Polyketidesmentioning
confidence: 94%
See 1 more Smart Citation
“…Recently, Page's research group discovered an enzyme (olivetolic acid cyclase, OAC), which is inactive itself, but works with TKS to produce olivetolic acid. Interestingly, these two proteins did not physically interact each other to form a protein complex, as was initially hypothesized (Gagne et al 2012). Hop (Humulus lupulus L.), which also belongs to the Cannabaceae family, is an essential component, along with barley and yeast, for the beer brewing industry.…”
Section: Phenylpropanoids and Polyketidesmentioning
confidence: 94%
“…Likewise, Gagne et al have co-expressed TKS and OAC from hemp in yeast. When these cells were fed exogenous hexanoic acid, olivetolic acid (0.48 mg/l) was produced (Gagne et al 2012).…”
Section: Translation Of the Knowledge From Plant Glandular Trichomesmentioning
confidence: 99%
“…Ferredoxin-like fold proteins are widely distributed in all domains of life and are associated with diverse biochemical functions, ranging from monooxygenases in actinorhodin biosynthesis in Streptomyces coelicolor (Sciara et al 2003) to noncatalytic ribosomal L30 proteins (Mao and Williamson 1999). Interestingly, tetracenomycin F2 cyclase, a polyketide cyclase in the biosynthetic pathway of the antibiotic tetracenomycin C that is produced by various Streptomyces species, also belongs to the ferredoxin-like fold (Thompson et al 2004), although sequence analysis suggests that the two ferredoxin-like fold polyketide cyclases arose independently in plants and bacteria (Gagne et al 2012).…”
Section: Emergence Of Reconfigured Catalytic Mechanismsmentioning
confidence: 99%
“…OAC catalyzes the C2-C7 intramolecular aldol condensation of a tetraketide intermediate, produced from an upstream type III polyketide synthase (PKS) yielding olivetolic acid (Gagne et al 2012). Ferredoxin-like fold proteins are widely distributed in all domains of life and are associated with diverse biochemical functions, ranging from monooxygenases in actinorhodin biosynthesis in Streptomyces coelicolor (Sciara et al 2003) to noncatalytic ribosomal L30 proteins (Mao and Williamson 1999).…”
Section: Emergence Of Reconfigured Catalytic Mechanismsmentioning
confidence: 99%
“…This process is generally catalyzed by a type III polyketide synthase (PKS) by carbonchain elongation and the subsequent cyclization of the highly reactive poly--keto intermediate (Schrö der, 1999;Austin & Noel, 2003;Abe & Morita, 2010). Recent studies have suggested that the biosyntheses of plant polyketides, such as the anthranoids (Abe et al, 2005;Abdel-Rahman et al, 2013) and cannabinoids (Taura et al, 2009;Gagne et al, 2012) produced by Aloe arborescens and Cannabis sativa, respectively, require additional enzymes for proper folding cyclization of the linear poly--keto intermediate to generate the final products, as in the cases of bacterial polyketide biosyntheses.…”
Section: Introductionmentioning
confidence: 99%